(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The major objective of this paper is pediment a new equation which can be used to obtain the total dissolved salts in the sand. This equation enables us to obtain the total dissolved salts by finding density of the watery solution resulting from dissolve any sample in distilled water. This equation shows very good results, so in this paper a new method is proposed to find the total dissolved salts by applying this equation which derived in this research without the need to use usual methods in finding those total dissolved salts. In this study, the proposed method uses the density variation between distilled water and the watery solution which is taken from the sand sample dissolved with distilled water. This proposed method will make the test of total dissolved salts more easily and quickly applied. The proposed method is equal or exceed in its reliability on other testing methods.